Gambaran kepuasan kerja pada pengemudi layanan jasa transportasi ojek online - Fajar Trisna Sanubari; Sofa Amalia (Cognicia, 2019)
The rise of transportation network companies in Indonesia  provides another alternative solutions for effective and efficient transportation needs for the community. However, like any organization can not be seperated from the conflict that accompanies along with it. On of them is related to job satisfaction. Job satisfaction is seen as a collectio of feelings or attitudes of individuals towards several aspect of their work. The purpose of this study was to determine the level of job satisfaction on online motorcycle taxi drivers in Kota Malang by using of quantitative descriptive approach. This study involved 181 online motorcycle taxi drivers with sample determination using purposive sampling technique. Data collections uses Minnesota Satisfaction Questionnaire short-form. Based on the analysis result show the level of job satisfaction of online motorcycle taxi drivers is categorized as low with percentage of 51.9% and 48.1% categorized as high. 2) this study also saw no significant difference in job satisfaction in term of work status and length of work (job status p=0.074; length of work p=0.201 with a significant level of 5%).